Impact of diamond mining on agricultural activities in the West Akim Abuakwa Sub-Region - Ofosu, George Kwame (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Science in Regional Planning.